PELAKSANAAN TUGAS DAN FUNGSI DINAS KESEHATAN KOTA KUPANG DALAM MENGAWASI KUALITAS DEPOT AIR ISI ULANG BERDASARKAN PERATURAN MENTRI KESEHATAN REPUBLIK INDONESIA NO 43 TAHUN 2014 TENTANG HIGIENE SANITASI DEPOT AIR MINUM (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The existence of Political Parties in the unitary State of the Republic of Indonesia (NKRI) cannot be separated from the climate of freedom that existed during the Dutch Colonial Government. Such freedom gives people space to form an organization, including Political Parties. In addition, the existence of Political Parties in the Unitary State of the Republic of Indonesia is also inseparable from the role of movements that aim to obtain freedom from the Dutch colonial government, also demanding independence. We can see this with the birth of the Parties before Independence. community’s need for drinking water that is of good quality and safe for consumption as well as in line with the development of free markets and competition in the business word, many business actors have set up refill drinking water depots which must comply wiht the Regulation of the Minister of Indonesia Number 43 of the Year 2014 concening Sanitation Hygiene of Drinking Water Depots. The purpose of this study was to determine the performance of the Kupang City Health Office in supervising the quality of refill drinking water depots and to find aut the factors that influencer the performance of the Kupang City Health Office. This research is empirical juridikal in nature, namely capturing the legal provisions that apply and what is happening in this case interviews to obtain an overview of data related to research problems. The sampling method used is purposive sampling, namely by choose informants who are considered knowledgeable and trustworthy to be data sources. The results of this study are the influence of tasks and functions of the health office in supervicing drinking water depots, seen from the large number of depots that do not have official business permits. The peformance of the kupang City Health Office in supervising the quality of refill drinking water depots is not good enough, and there is still a need for improvement in terms of productivity and also the need for member personnel to be equitablein monitoring activities.